2023
DOI: 10.3390/vaccines11010171
|View full text |Cite
|
Sign up to set email alerts
|

Rural Americans’ COVID-19 Vaccine Perceptions and Willingness to Vaccinate against COVID-19 with Their Community Pharmacists: An Exploratory Study

Abstract: In early 2022 in the U.S., rural adults were the least likely to vaccinate against COVID-19 due to vaccine hesitancy and reduced healthcare access. This study explored the factors influencing rural adults’ COVID-19 vaccine perceptions and their acceptance of pharmacist-administered vaccination. We utilized phone-based semi-structured interviews with 30 adults living in rural regions of one southwestern state and analyzed the data using a team-based thematic analysis approach. Vaccine-willing participants descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Additionally, it should be acknowledged that there were increased rates of skepticism regarding COVID-19 in rural communities [ 13 ]. For this reason, it has been documented that patients were not seeking medical attention when they potentially had COVID-19 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it should be acknowledged that there were increased rates of skepticism regarding COVID-19 in rural communities [ 13 ]. For this reason, it has been documented that patients were not seeking medical attention when they potentially had COVID-19 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jazan Province has a higher proportion of rural population than other regions of Saudi Arabia [19]. Many studies have revealed a disparity between rural and urban areas in the prevalence of vaccine reluctance [20,21]. According to these studies, rural societies often have less access to accurate information about vaccines due to limited internet access, less access to healthcare providers, and cultural barriers.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID‐19 vaccine rollout introduced another high‐priority challenge, further straining existing organizational structures and staffing capacity. Micropolitan and rural communities had significantly lower COVID‐19 vaccine rates throughout the pandemic, 5 and while many factors, including vaccine hesitancy, 6,7 could have contributed to this, issues related to access may be a factor 8 . Throughout the pandemic, private‐public partnerships emerged to provide vaccines in micropolitan and rural communities.…”
Section: Introductionmentioning
confidence: 99%